Proposta de aclaração do “pacto sucessório” à luz de novos dados - Abel Estefânio (Medievalista)
In an earlier work published in the Medievalista online Journal, the author considered that the designated “pacto sucessório” between the Counts Raymond and Henry could be a modern fake, although he had not been able to say that categorically. In the present paper, it is developed the study of the linguistic argument, which proved to be inconclusive. For this reason, it was necessary to continue the research on how the pact came into the hands of Luc D' Achery. The discovery of the manuscript that the benedictine monk of the congregation of St. Mauro published in the Spicilegium would prove to be decisive for the author to reconsider its position on the historical veracity of the document, arguing now that its data can be used as basis for a credible historical reconstruction. Accordingly, he presents a proposal of critical dating of the famous document between 1105-1107, based on internal elements of the text, significantly shortening the interval previously proposed by Rui Pinto de Azevedo in the Documentos Medievais Portugueses. On the other hand, the location and study of an unpublished document of Count Raymond contributes to clarify the context in which the agreement